Copper-Catalyzed Arylation of Benzothiazoles with Toluene Derivatives: Synthesis of 2-Arylbenzothiazole - Li, Chengliang; Deng, Hongmei; Jin, Tao; Liu, Zhiqiang; Jiang, Ruolan; Li, Chunju; Jia, Xueshun; Li, Jian (Synthesis, 2017)
A copper-catalyzed reaction of benzothiazole and readily available toluene derivatives has been disclosed. This protocol is proposed to proceed through the oxidation of toluene and ring opening of benzothiazole, thus providing a new pathway for the synthesis of 2-arylbenzothiazoles.
Keywords: toluene; oxidation; copper; benzothiazole; arylation